The overgrowth of urbanism and neighborhood-orientated - sahar safari; seyyed yaqoub mousavi (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2017)
The present research studies the effects of overgrowth of urbanism on the sense of belonging to the residence block. In this research, the concept of urbanism has been studied by emphasize on Louis Wirth’s theory of Urbanism, theories of Chicago School, Milan and Chavis’s Sense of Community theory, Place Identity theory of Ralph and Raoulz and Kasadra and Janowitz ‘s Systemic Theory. The sense of belonging to place as a dependent variable consists of objective, subjective, cognitive and emotional dimensions. Districts 2, 13 and 22 of Tehran City were selected at random from the 22 districts of Tehran as statistical population of the research. The methodology of the research is survey by using questionnaire technique. The data was collected from 391 individuals in +20 years old defined as statistical population. Ultimately, the collected data was studied by using Correlation Coefficient Analysis, Variance Analysis Test and Multi-variable Regression Analysis. Some of the most important results obtained from correlation among variables indicate negative and significant correlation between urban life style, inclination to practice expanded relations in the city and attachment to urban places, with sense of belonging to place. In addition, positive and significant correlation was found between length of residence, ownership type of residential house and sense of belonging to the place. In the meantime, a significant relationship was found between the variables of age and income of the individuals’ subject of study and their sense of belonging to their residence place.